Transformasi Digital Lembaga Keuangan Syariah: Peluang dan Implementasinya di Era Industri 4.0 - Qothrunnada, Nabila Azura; Iswanto, Juni; Fitrotus S, Dewi; Hendratri, Bhaswarendra Guntur; Subekan, Subekan (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The main problem with Sharia financial institutions (LKS) is the low literacy and inclusiveness of Sharia finance among the public, and this can be minimized with the digital transformation of LKS. Therefore, this research examines the challenges and implementation of digital transformation in LKS. The research method is a literature study that reviews and analyzes scientific publications related to digital transformation in the context of Islamic financial institutions. This research shows that opportunities for digital transformation by Sharia financial institutions include product innovation and service improvement. In contrast, product innovation includes diversification in financing and collection products, such as savings or investment. Digital transformation means that customers have many choices of LKS products. On the other hand, services by LKS are much easier and more extensive. Second, operational efficiency, risk management, and digital transformation allow LKS to monitor real-time transactions. Then, implementation of digital transformation in Sharia Financial Institutions, including strategic orientation, use of artificial intelligence and data analysis, organizational culture and security changes, and Sharia compliance.